1993
DOI: 10.1111/j.1469-8137.1993.tb03903.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of heavy metal tolerance and co‐tolerance in Deschampsia cespitosa (L.) Beauv. from European and Canadian populations

Abstract: By sampling soils and plants from a variety of metal-contaminated sites in Canada and Europe, heavy metal tolerance and co-tolerance have been investigated in the grass Deschampsia cespitosa L. (Beauv.). Soils were analyzed for water extractable Ca, as well as for their heavy metal content (Cu, Ni, Zn, Pb, Cd, Co), electrical conductivity, pH and organic matter. Canadian plant material was collected from non-contaminated areas, as well as sites contaminated by copper and nickel (Sudbury) and nickel and cobalt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…In fact, the closest sites are about 2 km away from each other and the most distant sites are >300 km apart. The clustering of Cobalt and Sudbury populations strengthens the earlier theory that Sudbury populations of D. cespitosa might be from the Cobalt region (Von Frenckell-Insam and Hutchinson, 1993;Gervais and Nkongolo, 2011).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In fact, the closest sites are about 2 km away from each other and the most distant sites are >300 km apart. The clustering of Cobalt and Sudbury populations strengthens the earlier theory that Sudbury populations of D. cespitosa might be from the Cobalt region (Von Frenckell-Insam and Hutchinson, 1993;Gervais and Nkongolo, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…If resistance to metal in an outcrossing and perennial species such as D. cespitosa is a quantitative trait, it is very likely that allelic frequency will be maintained over time (Von Frenckell-Insam and Hutchinson, 1993);MacNair, 1993). This is expected to result in a neutral genetic variation (Gervais and Nkongolo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference in Zn tolerance was very small for all three populations. Thus, any co-tolerance to Zn amongst Ni screened seedlings is very low and certainly not comparable to the level of co-tolerance observed among the Sudbury and Cobalt plants (von Frenckell-Insam and Hutchinson, 1993). Thus, it can be concluded that co-tolerance to Zn is not common to all Ni tolerant D. cespitosa populations.…”
Section: Tolerances and Co-tolerances Of Screened Seedlingsmentioning
confidence: 80%
“…In the summer of 1988, seeds from three D. cespitosa populations growing in uncontaminated soils were collected: from Baymouth, Cypress Lake (both in Ontario, Canada) and from Elm (located close to the Harz Mountains in the north-central part of Germany) (for complete soil analyses of the sample sites, see von Frenckell-Insam & Hutchinson, 1993). Seeds were stored in paper bags and stratified at 4 °C for a minimum of one month before the experiment, which tested 24000 seeds from each population.…”
Section: Collection Of Seed Materialsmentioning
confidence: 99%
“…Von Frenckell-Insam & Hutchinson (1993a) later suggested that coppernickel tolerance in this species is also not a result of cotolerance. In reality, the best way of distinguishing between linkage disequilibrium and pleiotropy is by a genetic analysis, through which the independence of genes for different metals can be studied (Macnair, 1993).…”
Section: Introductionmentioning
confidence: 99%